FATTY ACID PROFILES OF MICROALGAE ISOLATES FROM THE WATERS OF ITS DORMITORY POND IN SURABAYA, INDONESIA - Alfiyyana Nurrahma Mawardani; Dini Ermavitalini; Triono Bagus Saputro; Farid Kamal Muzaki; Adi Setyo Purnomo; Hery Purnobasuki (BIOTROPIA, 2025)
ARTICLE HIGHLIGHTS- Microalgae from ITS Dormitory Pond were identified using morphological analysis.- The study analyzed the fatty acid composition of four microalgae genera.- Dictyosphaerium had the highest total fatty acid content.- The findings suggest potential applications of these microalgae in biotechnology.- Further research is needed to improve fatty acid production. ABSTRACT Microalgae are a diverse group of autotrophic microorganisms classified into prokaryotic and eukaryotic groups. Their ability to thrive in various environmental conditions enables the identification of species with distinct fatty acid profiles. The absence of a microalgae culture collection at Sepuluh Nopember Institute of Technology (ITS) motivated the selection of the ITS Dormitory Pond as the research site. This study aimed to identify microalgae species present in the pond through morphological characterization and analyze their fatty acid profiles. Morphological identification was conducted using taxonomic references, while fatty acid composition was determined via GC-MS analysis. The results identified four genera: Dictyosphaerium, Vitreochlamys, Desmodesmus, and Chlorella. Their fatty acid profiles varied, comprising saturated (SFA), monounsaturated (MUFA), and polyunsaturated fatty acids (PUFA). Dictyosphaerium contained 17.57% SFA, 12.28% MUFA, and 0.33% PUFA, while Vitreochlamys had 10.83% SFA and 10.19% MUFA. Desmodesmus exhibited 14.19% SFA, 7.39% MUFA, and 4.14% PUFA, whereas Chlorella had 1.92% SFA and 2.67% PUFA. These findings highlight the potential of microalgae from ITS Dormitory Pond as a natural source of fatty acids. Further research is recommended to optimize culture conditions for enhancing commercially valuable fatty acid production.